Contexto familiar como factor predisponente para desarrollar diabetes mellitus tipo 2, en el Centro de Salud N° 2. - Vera Ramírez, Keyla María (2016)
The purpose of this project was to carry out an analysis regarding family background as a predisposing factor for developing diabetes mellitus type 2 in Loja's health center No.2. This study aims to determine family background as a predisposing factor for developing diabetes mellitus type 2 for which a quantitative, descriptive, cross-sectional study method was used, in which 50 patients who attended an external consultation in Loja's Health Center No.2 during the months of May, June and July 2015 participated. Through data collection techniques such as the survey, it was obtained that females represent 62.0%; from their history it is revealed that each of the patients are overweight or have some degree of obesity 74.0%; arterial hypertension 80.0%; polycystic ovary syndrome 16.0%; perform physical exercise 6.0%; consume alcohol 16.0%, consume tobacco 6.0%; patients with family who have diabetes mellitus 62.0%. In terms of risk factors present in the family's history it was discovered that obesity 58.0%; physical inactivity 56.0%; hypertension 62.0%; polycystic ovary syndrome 6.0%; inadequate food intake 52.0%; alcohol consumption 42.0% and tobacco consumption 30.0% were present. Using the data collected, a conclusion was determined that of all the risk factors present in the families of the surveyed patients, arterial hypertension was the most prevalent, however, it wais found in very similar proportions when compared to other risk factors. Palabras clave: diabetes mellitus type 2, familiar background, predisposing factor.